Culture media supplemented with inorganic salts improve the growth and viability of several bacterial strains - Nacsa-Farkas, Elvira; Kerekes, Erika Beáta; Hargitai, Fanni; Vágvölgyi, Csaba; Szegedi, Ernő (Acta Biologica Szegediensis, 2016)
In order to improve growth and storage conditions for bacterial cultures, commonly used basic culture media, Luria-Bertani broth (LB) and glucose-yeast extract (GY) were tested along with their supplemented versions (LBS and GYS) containing a complex set of inorganic salts required for common physiological processes. The growth kinetics and viability of 15 representative strains were compared on LB/LBS or GY/GYS. Growth kinetics were examined during a 24 h period. Five out of 15 strains showed enhanced growth on LBS and GYS. Three strains showed very low viability (3 months or lower) both on the basic and salt-supplemented media. Six strains could be equally recovered after 6 or 12 months both from LB/LBS and from GY/GYS. Six of the tested 15 bacterial strains showed significantly better recovery rate on the inorganic-supplemented media LBS or GYS than on basic LB or GY. These results show that inorganic supplement of basic media may significantly improve the growth and viability of several bacterial strains.